การจัดการความขัดแย้งเชิงสมานฉันท์กับบริการทางการแพทย์ในเขตกรุงเทพมหานครและปริมณฑลช่วงแพร่ระบาดของโรคโควิด-19 (พ.ศ. 2563 - 2564) - ปิยะวัฒน์ เด่นดำรงกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
This study explores conflict characteristics and management strategies that have not entered the primary juridical process. Conducted during the COVID-19 epidemic in tertiary care units in Bangkok and surrounding areas, the research sheds light on the potential application of restorative justice. Data collection involved questionnaires and in-depth interviews with individuals involved in medical disputes.Analysis of 19 hospital surveys revealed that inappropriate information provision and communication problems accounted for the majority of conflict-related issues (71.5%). Notably, only minority of mediators (12.2%) had formal training in mediation or conflict management, and none were familiar with the concept of restorative justice. In-depth interviews further highlighted that conflicts were associated to clients doubts about the service, resulting in damages and communication pitfalls, or issues related to the providers attitudes. Factors such as a lack of decision power, insincere mediation, unsympathetic service providers, and mismatched remedies should be considered in conflict resolutions. Successful reconciliation is linked with providing complainants with sufficient remedies and establishing successful, consistent communication. Executives are encouraged to actively participate in the management, prioritize workload considerations, facilitate skills training for mediators, and apply restorative justice principles, emphasizing a strategy focused on forgiveness.